2021
DOI: 10.3390/biology10070600
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of the MICOS Complex in Cristae Dynamics and Biogenesis

Abstract: Mitochondria are double membrane-enclosed organelles performing important cellular and metabolic functions such as ATP generation, heme biogenesis, apoptosis, ROS production and calcium buffering. The mitochondrial inner membrane (IM) is folded into cristae membranes (CMs) of variable shapes using molecular players including the ‘mitochondrial contact site and cristae organizing system’ (MICOS) complex, the dynamin-like GTPase OPA1, the F1FO ATP synthase and cardiolipin. Aberrant cristae structures are associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 105 publications
(189 reference statements)
1
40
0
Order By: Relevance
“…This proves the importance of CJ in maintaining the heterogeneity of ΔѰm between different regions of the IM, possibly by acting as a diffusion barrier for protons or other metabolites (Anand et al, 2021). It was also observed that cristae vesicles generated due to the detachment of CJ from the IBM in MIC10 or OPA1 KO cells had hyperpolarized mitochondria (Anand et al, 2021;Wolf et al, 2019). This could perhaps be extrapolated to MIC60 KD or KO cells although, experiments are needed to measure the changes in ΔѰm in cells subjected to MIC60 KD or KO.…”
Section: Mic60 Depletion Can Affect Mitochondrial Ros Levelsmentioning
confidence: 62%
See 4 more Smart Citations
“…This proves the importance of CJ in maintaining the heterogeneity of ΔѰm between different regions of the IM, possibly by acting as a diffusion barrier for protons or other metabolites (Anand et al, 2021). It was also observed that cristae vesicles generated due to the detachment of CJ from the IBM in MIC10 or OPA1 KO cells had hyperpolarized mitochondria (Anand et al, 2021;Wolf et al, 2019). This could perhaps be extrapolated to MIC60 KD or KO cells although, experiments are needed to measure the changes in ΔѰm in cells subjected to MIC60 KD or KO.…”
Section: Mic60 Depletion Can Affect Mitochondrial Ros Levelsmentioning
confidence: 62%
“…Studies reported previously that depletion in MICOS sub-units like MIC13, MIC10 or MIC60 could Discussion decrease the heterogeneity in the ΔѰm between CM and IBM. This proves the importance of CJ in maintaining the heterogeneity of ΔѰm between different regions of the IM, possibly by acting as a diffusion barrier for protons or other metabolites (Anand et al, 2021). It was also observed that cristae vesicles generated due to the detachment of CJ from the IBM in MIC10 or OPA1 KO cells had hyperpolarized mitochondria (Anand et al, 2021;Wolf et al, 2019).…”
Section: Mic60 Depletion Can Affect Mitochondrial Ros Levelsmentioning
confidence: 65%
See 3 more Smart Citations